Edukasi Penyusunan Laporan Keuangan Berbasis Digital Pada UMKM Usaha Batako UD Lancar Rejeki Di Desa Krogowanan, Kecamatan Sawangan - Anggi Oktavia Aryani; Endang Sri Utami (Jurnal Pelayanan Hubungan Masyarakat, 2023)
Technology is developing very fast, until now it has entered the digital era. Where UMKM actors are expected to be able to adapt and utilize technology for business progress. However, in reality, many UMKM actors find it difficult to adapt technology, so they still use manual methods which are less effective. Therefore, the purpose of this service is to help the UMKM Batako Business named UD Lancar Rejeki located in Krogowanan Village, Sawangan District, Magelang Regency, so that they can record their business financial transactions digitally using the BukuKas application via Smartphone. In its business processes, financial transactions at UD Lancar Rejeki are still recorded in a simple manner and are not in accordance with a standard structure. The method used in this activity is the direct mentoring method, which starts with providing socialization on the use of the Cash Book application, then direct practice until it is successfully implemented. Activities carried out smoothly and can provide insight and train the skills of partners in implementing digital-based financial reports. After the training activities are completed, partners are able to use the Cash Book application in recording transactions, making financial records and financial reports, and can find out the cost of goods sold and profit and loss